2020
DOI: 10.1080/17435390.2020.1839137
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxicological assessment of commercial boron nitride nanotubes toward Xenopus laevis tadpoles and host-associated gut microbiota

Abstract: assessment of commercial boron nitride nanotubes toward Xenopus laevis tadpoles and host-associated gut microbiota. (2021) Nanotoxicology, 15 (1). 35-51.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 115 publications
(118 reference statements)
0
4
0
Order By: Relevance
“…Apples, coffee, dry beans, milk, and potatoes are the five most prevalent sources of boron in a person’s daily diet. Boron intakes of 1–3 mg/day have been shown to improve bone and brain health in adults when compared to intakes of 0.25–0.50 mg/day [ 173 ]. The right amount of boron can help to create the intestinal organizational structure, which improves gastrointestinal absorption [ 173 ].…”
Section: Boron As a Neuroprotective Agentmentioning
confidence: 99%
“…Apples, coffee, dry beans, milk, and potatoes are the five most prevalent sources of boron in a person’s daily diet. Boron intakes of 1–3 mg/day have been shown to improve bone and brain health in adults when compared to intakes of 0.25–0.50 mg/day [ 173 ]. The right amount of boron can help to create the intestinal organizational structure, which improves gastrointestinal absorption [ 173 ].…”
Section: Boron As a Neuroprotective Agentmentioning
confidence: 99%
“…To date, very few studies focused on other 2D materials such as MoS 2 , WS 2 , or hBN. However, it has been reported that free boron present in tested boron-containing nanomaterials is beneficial for Xenopus tadpole metabolism …”
Section: D Materials Impact On Vertebratesmentioning
confidence: 99%
“…Thus, butyrate increases iodine uptake and the expression of thyroid hormone receptors in mice [200,201]. Regarding the nutritional intake of B, the most important research studies regarding the supplementation of the diet with B in animals and humans have shown the following: (a) healthy women fed with a diet rich in B (10 mg B per day) have a significant decrease of 25% in the thyroid-stimulating hormone (TSH, thyrotropin) level [202]; (b) B shows an iodine-like effect while investigating the influence on tail maturation of Xenopus laevis frogs, i.e., tail maturation in X. laevis is modulated by the thyroid axis [203,204]; (c) dietary supplementation with BA (400 mg/kg) during a 4-month period increased the level of triiodothyronine (T3) of the rams in the serum samples compared with control [205]. There were also some contradictory results, but in general, favorable effects were observed with the B diet in animals and humans [206].…”
Section: Microbiota-gut-immune Systemmentioning
confidence: 99%